1993
DOI: 10.1152/jn.1993.69.4.1276
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenesis in chronically injured cortex: in vitro studies

Abstract: 1. Field potentials and intracellular activities were examined in neocortical slices obtained through areas of chronic cortical injury produced by cortical undercutting and transcortical lesions made in vivo 7-122 days before the terminal in vitro slice experiment. 2. Abnormal field potentials characterized by long- and variable-latency multiphasic events could be evoked by layer VI-white matter or subpial stimulation in 9 of 15 animals that had adequate partial cortical isolations. These "epileptiform" field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
142
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 218 publications
(167 citation statements)
references
References 0 publications
25
142
0
Order By: Relevance
“…Therefore, additional factors should have been responsible for the increased amplitude of averaged postsynaptic responses in the undercut cortex. We found that neuronal input resistance in chronic conditions was increased, confirming previous findings obtained in vitro from chronically deafferented cortical neurons (Prince and Tseng, 1993;Tseng and Prince, 1996). In addition, we observed an increased number of spikes and instantaneous firing rate of neurons located in the traumatized cortex, supporting the hyperactivity of these neurons.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, additional factors should have been responsible for the increased amplitude of averaged postsynaptic responses in the undercut cortex. We found that neuronal input resistance in chronic conditions was increased, confirming previous findings obtained in vitro from chronically deafferented cortical neurons (Prince and Tseng, 1993;Tseng and Prince, 1996). In addition, we observed an increased number of spikes and instantaneous firing rate of neurons located in the traumatized cortex, supporting the hyperactivity of these neurons.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with a previous study (Prince and Tseng, 1993), the firing threshold of neurons in chronic undercut cortex was not different from control (data not shown).…”
Section: Neuronal Hyperexcitability After Traumasupporting
confidence: 93%
See 3 more Smart Citations